Motives and perceived benefits of learning translation: A preliminary investigation of non-native EFL student teachers - Christy Fung-ming LIU (Belas Infiéis, 2020)
The relationship between the teaching of English as a foreign language (EFL) and translation have been loosely entwined for a very long time. However, in the past decade, a number of academics have developed a renewed interest in the interplay between the two, and some teacher education universities offer translation courses to their student teachers. This paper presents findings from a preliminary study in which a questionnaire survey was used to identify the motives and perceived benefits of learning translation of 40 non-native EFL student teachers whose first language is Chinese, in a teacher education university in Hong Kong. The findings indicate that the pre-service teachers decided on taking translation courses or taking the subject as a minor because of their interest in both Chinese and English and their eagerness to improve their proficiency in these languages. The belief that learning translation might help non-native EFL student teachers secure a job in a language-related field is another prime motive for them to learn translation. It was discerned that they perceive learning translation to be beneficial to both their Chinese and English proficiency, especially in the knowledge of English grammar, and they have benefited in bilingual competence and career options. The paper concludes that although EFL student teachers tend not to work as professional translators after graduation, learning translation is deemed to have provided them with multifaceted benefits and increased their competitiveness in language-related fields.